Renouer avec l’esthétique de l’archive photographique - Bénichou, Anne (CV Photo)

(untitled) (Les Productions Ciel variable, 2002)
Abstract Since the 1960s, a number of Western art practices have revived the aesthetic of the photographic archive as it was developed in the nineteenth century. Starting from the work of Allan Sekula, the author distinguishes two aesthetic trends: the inventory and the classification. Whether arising from one or the other, use of the photographic archive seems to be a strategy through which contemporary artists redefine the limits of their field of activity, sometimes even infringing on areas of competency that are not traditionally theirs.